Peningkatkan Kemampuan Motorik Halus Anak Melalui Kegiatan Menyusun Daun di Tk Amanah Kabupaten Padang Pariaman - Zarina Rahmi, Dian; Hazizah, Nur (Penerbit Aksara Rentaka Siar (ARS), 2020)
Fine motor is the activity of coordinating muscles by demanding the ability to control fine movements and be able to apply in the surrounding environment or in everyday life so that aspects of a child's development can develop properly. The purpose of this study was to improve children's fine motor skills through leaf compilation activities in Group B of Padang Pariaman Kindergarten. This type of research is a classroom action research (Classroom Action). Data collection by observation while analyzed using a percentage formula. The results of research in the kindergarten Amanah Padang Pariaman that the child's fine motor skills increased from each meeting can be seen from the average in the first cycle 56.6% increased in the second cycle to 83.3% with the activities of arranging leaves in the children's fine motor skills